1997
DOI: 10.1016/s0022-5347(01)68155-2
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-Magnesium Citrate Is an Effective Prophylaxis Against Recurrent Calcium Oxalate Nephrolithiasis

Abstract: Potassium-magnesium citrate effectively prevents recurrent calcium oxalate stones, and this treatment given for up to 3 years reduces risk of recurrence by 85%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
2
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(186 citation statements)
references
References 6 publications
2
170
2
12
Order By: Relevance
“…Pharmacologic therapy is generally recommended for patients with high risk of recurrent stones (80,81). Thiazide or thiazidelike diuretics, citrate, and allopurinol reduce USD compared with placebo or control in patients with hypercalciuria, hypocitraturia, or hyperuricosuria, respectively (92)(93)(94)(95). Guidelines for pharmacologic USD management differ.…”
Section: Preventionmentioning
confidence: 99%
“…Pharmacologic therapy is generally recommended for patients with high risk of recurrent stones (80,81). Thiazide or thiazidelike diuretics, citrate, and allopurinol reduce USD compared with placebo or control in patients with hypercalciuria, hypocitraturia, or hyperuricosuria, respectively (92)(93)(94)(95). Guidelines for pharmacologic USD management differ.…”
Section: Preventionmentioning
confidence: 99%
“…Long-term thiazide treatment can cause hypomagnesaemia and hypomagnesuria, and supplements of magnesium might thus be of value. Promising results in preventing recurrence were reported in patients treated with potassium magnesium citrate [73].…”
Section: Magnesiummentioning
confidence: 99%
“…Several authors supported the benefit of alkaline citrates in all patients undergoing shockwave lithotripsy for the significant improvement in rates of alleviation the calcium oxalate stone-forming activity and positively influence the preexisting stone clearance and dissolution with minor adverse reaction (2,11,(14)(15)(16). The studies with stone recurrence as the endpoint demonstrated a reduction in stone-forming rate from 47% to 100%.…”
Section: Discussionmentioning
confidence: 99%